Results of risk assessment of alien species in Sweden 2018 - Swedish Species Information Centre, Swedish University of Agricultural Sciences (Swedish University of Agricultural Sciences, 2025)
The Swedish Species Information Centre estimated for 1033 species their potential risks concerning native biodiversity in Sweden. The assignment was performed on behalf of the Swedish Environmental Protection Agency and the Swedish Agency for Marine and Water Management in 2017-2018. This dataset contains the results of this risk assessment that was conducted according to the GEIAA v3.3 method. The results presented are impact category and criteria for impact assessment, and assessments of ecological effect and invasion potential.

Artdatabanken har på uppdrag av Naturvårdsverket och Havs- och vattenmyndigheten riskklassificerat 1033 arter under 2017-2018. Risken avser sannolikheten att de utgör, eller kan komma att utgöra, en risk för inhemsk biologisk mångfald. Det här datasetet innehåller resultat för genomförd riskklassning som utfördes enligt metoden GEIAA v.3.3. De resultat som återges är uppskattningar av ekologisk effekt och invasionspotential, samt riskklass och utfallsgivande kriterier.
Resultat av riskklassificering av främmande arter i Sverige 2018
Risklista Sverige 2018
Keywords: risk assessment; riskvärdering; risk assessment; invasive species; alien species; alien plant; invasive alien species; introduced species; främmande arter; Animalia; flercelliga djur; Fungi; svampar; Chromista; kromister; Plantae; egentliga växter; Botany; Botanik; Zoology; Zoologi; Ecology; Ekologi; Other Biological Topics; Annan biologi